2014
DOI: 10.1186/s12934-014-0177-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome engineering for improved recombinant protein expression in Escherichia coli

Abstract: A metabolic engineering perspective which views recombinant protein expression as a multistep pathway allows us to move beyond vector design and identify the downstream rate limiting steps in expression. In E.coli these are typically at the translational level and the supply of precursors in the form of energy, amino acids and nucleotides. Further recombinant protein production triggers a global cellular stress response which feedback inhibits both growth and product formation. Countering this requires a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 194 publications
0
76
0
Order By: Relevance
“…A situation unlikely to change significantly as E. coli systems are continuously revisited, being easy to engineer and adapt to new constraints, such as antibiotic-free selection. 1,54 Some alternative gram-negative hosts have been investigated, including Pseudomonas fluorescens, 55 for which a complete toolbox is available, although its utility remains marginal compare with E. coli. Other hosts, known for their high metabolite output, are currently being explored, including Ralstonia eutropha, although with the essential limitation that there are no suitable selection markers, no replicons and more generally no basic genetic elements identified yet for this type of host.…”
Section: Bacteria: Between Evolution and Revolutionmentioning
confidence: 99%
“…A situation unlikely to change significantly as E. coli systems are continuously revisited, being easy to engineer and adapt to new constraints, such as antibiotic-free selection. 1,54 Some alternative gram-negative hosts have been investigated, including Pseudomonas fluorescens, 55 for which a complete toolbox is available, although its utility remains marginal compare with E. coli. Other hosts, known for their high metabolite output, are currently being explored, including Ralstonia eutropha, although with the essential limitation that there are no suitable selection markers, no replicons and more generally no basic genetic elements identified yet for this type of host.…”
Section: Bacteria: Between Evolution and Revolutionmentioning
confidence: 99%
“…Much of our understanding of bacterial and yeast life cycles stems from monitoring their proliferation in time and the most routine way of doing so is using optical density (OD) measurements. The applications of such measurements range from routine checks during different cloning techniques 1 ; through studying cellular physiology and metabolism 2,3 ; to determining the growth rate for antibiotic dosage 4,5 ; and monitoring of biomass accumulation during bio-industrial fermentation 6 . Here we introduce a set of calibration techniques that take into account the relevant parameters affecting OD measurements, including at high culture densities, in a range of conditions commonly used by researchers.…”
mentioning
confidence: 99%
“…Early evidence of the effect of RNA structures on translation initiation has been reported for the lysozyme gene of bacteriophage T4 [Knight et al, 1987], E. coli galE [Merril et al, 1981] and lamB genes [Hall et al, 1982], among others, and systematic and qualitative analyses of the influence of the stability and position of RNA secondary structures near the SD sequence on translation initiation have been performed by de Smit and van Duin [1990a, b], Studer and Joseph [2006], and Osterman et al [2013]. Last year, Mahalik et al [2014] revised a list of variables required to improve gene expression in E. coli and demonstrated that translation initiation in the presence of stable mRNA secondary structures could be a bottleneck for protein expression.…”
Section: Discussionmentioning
confidence: 99%